Factors influencing Malaysian public sector employees' performance - Aziz, Faiq; Muzlan, Norainnie; Ahrari, Seyedali; Zixuan, Dong (Seybold Publications, 2022)
Nowadays, the phenomenon of increased competition between organizations and their need to respond effectively to rapidly changing operational conditions, as well as to personnel requirements, has escalated the necessity to identify those factors that affect employee performance. Thus, this study aims to determine factors influencing employee performance of Malaysian Public Service employees. This study involved a total of 400 government personnel from 27 Malaysian ministries and departments. Correlation analysis and regression analysis were used. The study data is analyzed using SPSS. Results of the study found that there is a positive and significant relationship between recognition and job security towards employee performance. Multiple regression analysis found that job security had the strongest influence on employee performance, and recognition had the least influence on employee performance. The conclusions of this research have important practical implications, notably in the areas of policy formation and reference in the domain of human resource development expertise, among other things.